Pengaruh Penambahan Abu Ampas Tebu dan Kapur Terhadap Karakteristik Tanah Lempung Ekspansif (Studi Kasus : Tanah di Bojonegoro) - Yanwar Eko Prasetyo; Yulvi Zaika; Arief Rachmansyah (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2018)
In each region having different types of soil, one type of soil is expansive clay. In Indonesia, more than 1/5 of the land area in Indonesia are an expansive clay. This type of soil will affected by changes in water content and experience significant shrinkage. Therefore, to improve the soil and minimize shrinkage growth, an effort is needed, one of which is soil stabilization. Physical testing of soil with soil samples in the district Ngasem, Kab. Bojonegoro which is expansive clay soil shows that the CBR value is 3.953%, and the swelling value is 6.1858%. With such physical conditions with low carrying capacity it is necessary to stabilize the soil on clay in Bojonegoro. Stabilization efforts carried out are by chemical stabilization by mixing soil samples with additives in the form of bagasse and lime ash. The results of the physical soil test from the preliminary research conducted by the author by mixing bagasse ash in the soil with variations in levels of 8%, 10%, 12%, 14% showed a mixture of 8% bagasse ash was the optimum level for repairs to the soil. So it is used a mixture of 8% bagasse ash with the addition of variations in lime content of 4%, 6% and 8% of the total weight of the mixture. A mixture of 8% bagasse ash and 6% lime content produced a CBR value of 9,324%, this CBR value increased to 135.87%. While the swelling value is 0.1681%, with the same mixture level. This swelling value decreased to 97.28%. For the value of free development it decreased to 217.7% from the previous one which amounted to 70.59% to 22.22%.